1996
DOI: 10.1016/0735-1097(96)00102-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of angioscopy, intravascular ultrasound imaging and quantitative coronary angiography in predicting clinical outcome after coronary intervention in high risk patients

Abstract: Angioscopic plaque rupture and thrombus were independently associated with adverse outcome in patients with complex lesions after interventional procedures. These features were not identified by either angiography or intravascular ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 34 publications
0
40
0
1
Order By: Relevance
“…In the present case, angioscopy was not only more efficient in detecting intracoronary thrombus than angiography and IVUS, [20][21][22][23] but also allowed detailed observation of the degree of dilatation of the implanted coronary stent. Only intracoronary angioscopy could detect the cause of the repeat subacute thrombosis after stenting that resulted in AMI.…”
Section: Discussionmentioning
confidence: 91%
“…In the present case, angioscopy was not only more efficient in detecting intracoronary thrombus than angiography and IVUS, [20][21][22][23] but also allowed detailed observation of the degree of dilatation of the implanted coronary stent. Only intracoronary angioscopy could detect the cause of the repeat subacute thrombosis after stenting that resulted in AMI.…”
Section: Discussionmentioning
confidence: 91%
“…E) Ultra-som como método de monitoração de uma intervenção coronariana percutânea (stents) -O ultra-som é capaz de detectar alterações na luz do vaso, que, apesar de relativamente pequenas (em média de 0,5 mm), apresentam impacto clínico significativo. Essas alterações poderiam determinar condutas distintas, seja durante o implante, elevando a pressão de impactação da endoprótese na parede do vaso, aumentando o calibre do balão ou, quando da realização da cinecoronariografia tardia, auxiliando na decisão de revascularizar o vaso previamente tratado 50 .…”
Section: -Indicações Clínicas Do Ultra-som Intracoronarianounclassified
“…[3][4][5][6] These features have been associated with death, reinfarction, or need for repeat revascularization when lesions were treated within 17 days of the index event (risk ratio of 6.6 to 10.15). 4, 5 The presence of angioscopically detected thrombus or ruptured plaque preceding coronary intervention is associated with an increased rate of restenosis (52% to 54%) as well as a higher incidence of total occlusion at follow-up (4% to 7%). 7 Van Belle et al 1 have now demonstrated that these unfavorable lesion features persist for at least 1 month after the index event in many patients.…”
Section: See P 26 Commentarymentioning
confidence: 99%